2012 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2012
DOI: 10.1109/ceidp.2012.6378853
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tree inhibition by voltage stabilizers

Abstract: Electrical treeing is one of the main degradation mechanisms in polymer dielectrics at highly divergent electric fields and can, if initiated, cause dielectric breakdown as soon as an electrical tree channel has bridged the insulation. One way of increasing resistance to electrical treeing is the addition of certain organic additives such as polycyclic aromatic compounds or benzophenone-like structures. These additives act as voltage stabilizers that are believed to capture high energy electrons and dissipate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
3
14
0
Order By: Relevance
“…As the result, for benzophenonelike molecules, with increasing of number of heteroatom (O atom) and alkyl, E g decreases significantly. The calculated results explained well the reports by Jarvid , Englund , and their co-workers [8,9] that the introduction carbonyl and alkoxy into benzophenone molecules is an exciting molecular design because they can effectively decrease E g value and possess excellent compatibility with polymers matrix, e.g., E g of Bzo (4.44 eV) and Bd (4.22 eV) are smaller than that of Bz (4.90 eV). At the same time, E g of Mm (4.50 eV) is smaller than that of Bz too.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As the result, for benzophenonelike molecules, with increasing of number of heteroatom (O atom) and alkyl, E g decreases significantly. The calculated results explained well the reports by Jarvid , Englund , and their co-workers [8,9] that the introduction carbonyl and alkoxy into benzophenone molecules is an exciting molecular design because they can effectively decrease E g value and possess excellent compatibility with polymers matrix, e.g., E g of Bzo (4.44 eV) and Bd (4.22 eV) are smaller than that of Bz (4.90 eV). At the same time, E g of Mm (4.50 eV) is smaller than that of Bz too.…”
Section: Resultssupporting
confidence: 86%
“…Yamano , Englund , and their co-workers [7,8] reported that the addition of polycyclic aromatic hydrocarbons is effective for inhibiting the polymer molecule chain fracture caused by electron bombardment, thus increasing the initial voltage of electrical tree of polyethylene (PE) and inhibiting the electrical tree initiation. In 2012, a benzil type compound was evaluated as voltage stabilizer in a superclean XLPE by Jarvid and co-workers [9]. It shows that the investigated voltage stabilizer raises the electrical tree inception level significantly.…”
mentioning
confidence: 99%
“…It should at the same time be noticed that a higher concentration of antioxidant yields a higher tree inception voltage. Similar effect has been observed when adding voltage stabilizers to polyethylene [15]. A possible explanation of the observed effect could be that with the addition of substances that increase the field dependence of the conductivity -in this particular case the antioxidant -the field at the wire electrode surface becomes less than the capacitive field and therefore the local heating that can start the growth of electric trees will be pushed to higher voltage level [29].…”
Section: Materials Analysessupporting
confidence: 64%
“…Instead of the needle electrode, it makes use of a thin tungsten wire attached to a semiconducting tab for generating the highly divergent field in the surrounding polymeric material. Recently this idea has been developed further by removing the semi-conducting tab [15], which allowed to further reduce the time needed for sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Ester liquids can be used as an alternative to mineral oil in transformers [24]. Benzil and 4,4'-dihydroxy benzil have been evaluated as voltage stabilizers to resist electrical treeing in polymer dielectrics [25]. 2,3-heptanedione is included in this study to be compared with benzil that has two phenyl groups in its structure.…”
Section: A Ionization Potentialmentioning
confidence: 99%